2022
DOI: 10.1016/j.xjidi.2021.100064
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Adipose Tissue in the Pathogenesis of Psoriasis and Atopic Dermatitis in Obesity

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 110 publications
(180 reference statements)
2
34
0
Order By: Relevance
“…Further understanding of the role of this ecosystem in psoriasis and obesity interplay could lead to new therapies still to be developed. Probiotics have been demonstrated to improve psoriasis by modulating the two main parameters of gut microbiota: Alpha and Beta diversity [ 137 ], putting down roots in the quasi-causal role of dysbiosis in the psoriasis pathogenesis in people with obesity. Furthermore, several by-products from gut microbiota metabolism interfere in IL-17 and IL-23 [ 138 ] signalling pathways, whereby microbiota modulates keratinocytes and immune cells [ 95 ].…”
Section: The Link Between Psoriasis and Obesitymentioning
confidence: 99%
“…Further understanding of the role of this ecosystem in psoriasis and obesity interplay could lead to new therapies still to be developed. Probiotics have been demonstrated to improve psoriasis by modulating the two main parameters of gut microbiota: Alpha and Beta diversity [ 137 ], putting down roots in the quasi-causal role of dysbiosis in the psoriasis pathogenesis in people with obesity. Furthermore, several by-products from gut microbiota metabolism interfere in IL-17 and IL-23 [ 138 ] signalling pathways, whereby microbiota modulates keratinocytes and immune cells [ 95 ].…”
Section: The Link Between Psoriasis and Obesitymentioning
confidence: 99%
“…Their results indicated a causal role of adiposity in the development of AD, and suggested that obesity is a risk factor and a facilitator for the development of AD. Although the mechanism that links obesity and AD is unknown, available data suggest that a chronic inflammatory state caused by free fatty acids, adipokines, and adipocytokines from adipocytes and other local cells can mediate the increased risk of AD in obese patients [ 88 ]. Our findings are the first to show that changes induced by IgG from AD patients also affect miRNA expression in thymocytes, thus influencing their metabolism in AD.…”
Section: Discussionmentioning
confidence: 99%
“…The adipose tissue is responsible for the active secretion of several bioactive molecules whose effects can spread systemically and play a relevant role in the pathways implicated in psoriatic inflammation [ 184 ].…”
Section: Higher Prevalence Of Traditional CV Risk Factors In Psoriasi...mentioning
confidence: 99%
“…For instance, free fatty acids, which are abundantly released from the adipose tissue of patients with obesity, have been shown to exert a proinflammatory role and to worsen psoriasis in murine models, at least partly via activation of keratinocytes [ 184 ]. Moreover, adipokines, cytokines secreted by the adipose tissue, have been demonstrated to interfere with the function of several cell types.…”
Section: Higher Prevalence Of Traditional CV Risk Factors In Psoriasi...mentioning
confidence: 99%
See 1 more Smart Citation